2012
DOI: 10.1111/febs.12061
|View full text |Cite
|
Sign up to set email alerts
|

GsmR, a response regulator with an HD‐related output domain in Xanthomonas campestris, is positively controlled by Clp and is involved in the expression of genes responsible for flagellum synthesis

Abstract: In prokaryotes, two-component signal transduction systems, consisting of a histidine kinase and a response regulator, play a critical role in regulating a range of cellular functions. A recent study suggests that XCC3315, a response regulator with a CheY-like receiver domain attached to an uncharacterized HD-related output domain (HDOD domain), plays a role in the general stress response of the Gram-negative bacterium Xanthomonas campestris pv. campestris (Xcc), the causal agent of black rot in cruciferous pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
10
0
2
Order By: Relevance
“…Clp has been well studied as a cyclic di‐GMP‐responsive transcriptional regulator that plays essential roles in virulence factor production and the DSF signalling network in Xcc (He et al ., ; Chin et al ., ; Tao et al ., ). In most cases, Clp acts a transcriptional activator in Xcc (He et al ., ; Liu et al ., ). The present study demonstrated that Clp acts as a repressor in the regulation of rpfB expression (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Clp has been well studied as a cyclic di‐GMP‐responsive transcriptional regulator that plays essential roles in virulence factor production and the DSF signalling network in Xcc (He et al ., ; Chin et al ., ; Tao et al ., ). In most cases, Clp acts a transcriptional activator in Xcc (He et al ., ; Liu et al ., ). The present study demonstrated that Clp acts as a repressor in the regulation of rpfB expression (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…campestris ATCC 33913, four RR genes had been demonstrated in the full virulence for Xcc ( Qian et al, 2008b ). To date, 20 TCS proteins have been identified to be related to pathogenesis of Xanthomonas , including eight pairs of typical TCSs, RpfC-RpfG ( Tang et al, 1991 ), RaxH-RaxR ( Burdman et al, 2004 ), PhoQ-PhoP ( Lee et al, 2008 ), ColS-ColR (also named VgrS-VgrR) ( Qian et al, 2008b ; Zhang et al, 2008 ; Noh et al, 2014 ; Wang et al, 2016 ), RavS-RavR ( He et al, 2009 ), PdeK-PdeR (also named RavA-RavR) ( Yang et al, 2012 ; Tao et al, 2014 ), HpaR2-HpaS ( Li R.F et al, 2014 ), PcrK-PcrR ( Wang et al, 2017 ), four orphan RRs HrpG ( Wengelnik et al, 1996 ), VemR ( Tao and He, 2010 ), BfdR ( Huang et al, 2013 ), GsmR ( Liu et al, 2013 ), and XerR (also named XmbR and XibR) ( Wang et al, 2011 ; Yaryura et al, 2015 ; Pandey et al, 2016 ). The TCSs modulate the expression of several virulence factors through diverse molecular mechanisms such as interacting with DNA, protein-binding and involvement in second messenger metabolism, which generates a high level of regulatory versatility ( Qian et al, 2008a ; Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…An HDOD RR, GsmR, was recently characterized from Xanthomonas campestris , and found to regulate the expression of motility related genes. GsmR lacked the conserved His in the active site, and also lacked phosphatase or phosphodiesterase activity (Liu et al, 2013). DVU0330 has the conserved HD active site residues (Figure 1C), and here we showed that the isolated domain has weak PDE activity with bis- p NPP and none with c-di-GMP or any of the other substrates.…”
Section: Discussionmentioning
confidence: 99%